Simulation-Based E-Learning Framework for Entrepreneurship Education and Training - Constanţa-Nicoleta Bodea; Radu Ioan Mogoş; Maria-Iuliana Dascălu; Augustin Purnuş; Narcisa Georgeta Ciobotar (Amfiteatru Economic Journal, 2015)
The paper proposes an e-Learning framework in entrepreneurship. The framework has three main components, for identification the business opportunities, for developing business scenarios and for risk analysis. A common database assures the components integration. The main components of this framework are already available; the main challenging for those interested in using them is to design an integrated flow of activities, adapted with their curricula and other educational settings. The originality of the approach is that the framework is domain independent and uses advanced IT technologies, such as recommendation algorithms, agent-based simulations and extended graphical support. Using this e-learning framework, the students can learn how to choose relevant characteristics/aspects for a type of business and how important is each of them according specific criteria; how to set realistic values for different characteristics/aspects of the business, how a business scenario can be changed in order to fit better to the business context and how to assess/evaluate business scenarios.
Keywords: L26; M13; C15; 330; e-learning; entrepreneurial; competences; software agents; simulations; risk analysis; business opportunities; business scenarios